The prevalence of obesity-related hypertension among middle-aged and older adults in China - Zhang, Yang; Zhang, Wen-Qiang; Tang, Wei-Wei; Zhang, Wen-Yong; Liu, Jian-Xiong; Xu, Rong-Hua; Wang, Tzung-Dau; Huang, Xiao-Bo (Frontiers in Public Health, 2022)
Objective: The aim of our study was to assess the prevalence and geographic variation of obesity-related hypertension in China among adults aged 45 years or older. Methods: Data were derived from the China Health and Retirement Longitudinal Study (CHARLS) conducted in 2015. Stratified sample households covered 150 counties/districts and 450 villages/urban communities from 28 provinces by using household questionnaires, clinical measurements, and blood-based bioassays. Multivariable non-conditional logistic regression model was used to analyze the risk factors correlated with obesity-related hypertension. Results: The prevalence of obesity-related hypertension was 22.7%, approximately 120 million people, among adults aged 45 years or older in China. For people in the age ranges of 45–54, 55–64, 65–74, and ≥75, the prevalence of obesity-related hypertension were 16.7%, 24.3%, 27%, and 26.7% and the prevalence of obesity-related hypertension among hypertensive participants were 66.0%, 60.9%, 54.2%, and 47.3%, respectively. Compared with non-obesity-related hypertension, the obesity-related hypertensive patients had a higher prevalence of diabetes mellitus, dyslipidemia and hyperuricemia (all P < 0.0001). The prevalence of obesity-related hypertension showed a decreasing gradient from north to south and from east to west. Multivariate logistic regression analysis showed that female gender, living in urban areas, diabetes mellitus, dyslipidemia and hyperuricemia were positively correlated with obesity-related hypertension. Conclusion: The prevalence of obesity-related hypertension among adults aged 45 years or older was high in China. Among hypertensive participants, older age was negatively correlated with obesity-related hypertension. Obesity-related hypertensive participants are more prone to aggregation of risk factors of atherosclerotic cardiovascular disease.